From Islamophobia to Islamistophobia: framing Islamic movements in Egyptian newspapers after the January 25th Revolution - El-Haddad, Aisha Essam (AUC Knowledge Fountain, 2013)
This study examined how Egyptian newspapers framed Egyptian Islamic movements in the two years following the January 25, 2011 revolution. A content analysis was conducted on four newspapers including the state-owned Al-Ahram and three private newspapers representing different levels of professionalism: Al-Masry Al-Youm, Al-Youm Al-Sabea’ and Al-Dostor. The total sample consisted of 197 front-page news articles. Results indicated that Egyptian newspapers predominantly associated Islamism with negative values. Among the top five frames that dominated Egyptian newspapers coverage of Islamists – “anti-democracy”, “politically organized”, “violence”, “polarization”, and “anti-revolution” – four were negative. The study found framing differences across Islamic groups, especially between the Muslim Brotherhood and the Salafi Al-Noor party. Negative framing was more common in private newspapers scoring lower on professional and ethical standards. Results suggest that Islamists were already framed negatively before they reached power, and when their political roles changed framing became more negative. The study provides a reference point for future comparisons with the framing of Islamic movements in Egypt following the removal of President Mohammed Morsi on July 3, 2013.